Inside organizations : exploring organizational experiences - Coghlan, David (London : SAGE Publications Ltd, 2016)
Moving away from the common/traditional focus on studying organizations from a distance, this highly engaging book introduces the idea of studying them from the inside. Inside Organizations: Exploring Organizational Experiences guides placement students, and any student undertaking part-time work in an organization, through 'insider inquiry', helping them to develop key reflexive and critical thinking skills for their future careers. . It encourages you to pay attention to what goes on in organizations, to question what you experience and ultimately to make sense of how organizations function. , helping you to develop key reflexive and critical thinking skills for your future careers. This book is ideal for students on programmes with a placement or internship element such as business and management, nursing and health, and education and is especially useful to those doing reflective journals and essays.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Organizational change; Organizational learning